1999
DOI: 10.1097/00005392-199905000-00093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acetylic Salicylic Acid and Pentoxifylline on the Efficacy of Intravesical BCG Therapy in Orthotopic Murine Bladder Cancer (Mb49)

Abstract: The efficacy of BCG therapy in murine orthotopic bladder cancer is dependent on BCG viability and is not compromised by ASA or POF. Clinical trials to evaluate the efficacy of routine ASA or POF to reduce BCG side effects in patients, using self-assessment criteria, should be initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A drug delivery system that could promote uptake into the urothelium and, thus, form a controlled release depot would be of great therapeutic benefit. Often, intravesical administration of chemotherapeutics occurs immediately after transurethral resection of the tumor for cases involving low grade noninvasive bladder cancer; however, tumor reimplatation and subsequent tumor regrowth typically occurs at these traumatized sites. , Recent and ongoing studies in our laboratory have demonstrated that paclitaxel-loaded HPGs effectively increased the drug partitioning into bladder tissue in an ex vivo model. Furthermore, it has been shown that anionic, carboxylate bearing polyamidoamine dendrimers are readily taken up by endocytosis .…”
Section: Resultsmentioning
confidence: 99%
“…A drug delivery system that could promote uptake into the urothelium and, thus, form a controlled release depot would be of great therapeutic benefit. Often, intravesical administration of chemotherapeutics occurs immediately after transurethral resection of the tumor for cases involving low grade noninvasive bladder cancer; however, tumor reimplatation and subsequent tumor regrowth typically occurs at these traumatized sites. , Recent and ongoing studies in our laboratory have demonstrated that paclitaxel-loaded HPGs effectively increased the drug partitioning into bladder tissue in an ex vivo model. Furthermore, it has been shown that anionic, carboxylate bearing polyamidoamine dendrimers are readily taken up by endocytosis .…”
Section: Resultsmentioning
confidence: 99%
“…181920 In orthotopic bladder cancer models autoclaved BCG had no antitumor effect and the magnitude of the antitumor/immune response correlated with BCG viability. 21 In the clinical setting a direct correlation between therapeutic efficacy and BCG viability was observed. 4 While highlighting the relevance of BCG viability, no prior studies have provided mechanistic insight into how bacterial viability influences the tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial showed that though mitomycin C improved therapeutic efficacy of BCG, it also increased toxicity among mid and high risk NMIBC patients, which mitigate its chance to be further explored as a safe intervention [91]. In a murine model, acetylic salicylic acid and pentoxifylline seem to be effective in improving BCG efficacy [92]. In a systemic meta-analysis, it was concluded that compared to BCG alone, the synergistic effect of intravesical BCG and chemotherapy improved recurrence free survival, overall survival and disease specific survival with significantly decreased rate of fever, irritative symptoms and hematuria therapy among NMIBC patients [93].…”
Section: Intravesical Immunotherapy With Bcgmentioning
confidence: 99%